Analisis Niat Perilaku Gen-Z Menggunakan UTAUT2 Dengan Kepuasan Sebagai Moderasi : Studi Kasus Aplikasi Seabank - Indriani Nurfitri; Arny Lattu; M. Anton Permana (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
Lifestyle changes that are shifting towards digital have encouraged the financial sector to accelerate the transformation process towards digital finance known as financial technology, one of which is the Seabank application. This study was conducted with the aim of analyzing the factors that influence Gen-Z regarding satisfaction with behavioral intentions (Behavioral Intention) of using Seabank using quantitative methods by distributing questionnaires. The study used a modified UTAUT2 model by adopting only 5 of the 7 variables, namely performance expectancy, effort expectancy, social influence, facilitating conditions, and habits with the addition of one variable modification, namely trust as factors that have the potential to influence the moderating variable of user satisfaction (User Satisfaction) on behavioral intentions (Behavioral Intention) as a decision to use Seabank in the future. Data analysis used the SEM-PLS technique with the SMART PLS 3.0 application, with a total of 302 respondents who met the criteria.